Nitrogen Cycling and Management for Romaine and Crisphead Lettuce Grown on Organic Soils - Luis Santos; Alan L. Wright; Yigang Luo; Huangjun Lu; Dennis Calvin Odero (EDIS)
Lettuce has rapid growth and reaches harvest in 60–70 days in South Florida. This leads to high demands for nitrogen fertilization during the short growing season. A good N fertilization scheme should reduce costs, conserve natural resources, and minimize negative environmental impacts. The keys to using fertilizer efficiently are understanding the crop nutrient requirements to predict fertilizer needs and management as well as knowing the appropriate amounts to apply. Lettuce growers also need to know the nutritional status of the crop through soil and plant tissue testing. This 4-page fact sheet was written by Luis Santos, Alan L. Wright, Yigang Luo, Huangjun Lu, and D. Calvin Odero, and published by the UF Department of Soil and Water Science, September 2013.